STUDI LITERATUR: DAFTAR PUSTAKA DALAM PEMBUATAN KARYA ILMIAH - Verdianto, Verdianto; Muspawi, Mohamad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
A bibliography is an important element in writing scientific work which functions to identify the sources used in preparing an essay. According to the Big Indonesian Dictionary, a bibliography is a list that includes book titles, names of authors, publishers and other relevant information arranged alphabetically. Writing a bibliography not only functions as a reference source of information, but also as an appreciation for the author of the work used as a reference and as a way to maintain the professionalism of the author. This research uses a literature review method to analyze existing theories regarding bibliography, by collecting data from books, scientific journals and related articles taken from various databases, such as Google Scholar and Sinta Kemdikbud. This research reveals that bibliography has several functions, including strengthening arguments in scientific works, providing direction for readers who wish to check sources further, and maintaining the integrity and credibility of written works. Apart from that, this research also highlights the importance of a proper understanding of the elements that must be included in writing a bibliography, such as author's name, title, year of publication, and other publication information. Thus, writing a good bibliography is an indicator of professionalism and quality in scientific writing.